Optimization of the outlet unloading structure to prevent gaseous cavitation in a high-pressure axial piston pump. (April 2022) - Zhang, Bin; Zhao, Chunxiao; Hong, Haocen; Cheng, Guozan; Yang, Huayong; Feng, Shibo; Zhai, Jiang; Xiao, Wenhui
Raising the pressure rank of axial piston pumps is an effective way to enhance the power density. However, when hydraulic fluid switches between the suction and discharge areas in the valve plate at a high level of pressure, the effective delivery flow rates of pumps decrease and may cause vibrations, noise and gaseous cavitation. Increasing the inlet pressure is a common method used to reduce gaseous cavitation; however, this requires additional equipment to pressurize the inlet line, which reduces the power density of the pump. This study proposed a new approach to reduce gaseous cavitation by modifying the shape of the unloading holes for pumps. A computational fluid dynamics (CFD) model was established to examine the influences of the unloading holes of the valve plate on gaseous cavitation. The simulation results revealed that a crescent-shaped unloading hole in the valve plate can effectively decrease the gaseous cavitation by redistributing the damage power of cavitation. Moreover, the crescent-shaped design of the unloading hole can increase the unloading rate by 64.39% at an inlet pressure of 1.1 MPa and rotational speed of 1600 r/min compared to that of traditional unloading holes. As a result, cavitation in the pump can be reduced effectively by an improved unloading rate, which has great practical significance for suppressing the cavitation phenomenon and decreasing vibration and noise in the pump.